Compact Spacelike Surfaces in the 3-Dimensional de Sitter Space - Borisenko, A.A. (Журнал математической физики, анализа, геометрии, 2006)
We establish several sufficient conditions for a compact spacelike surface in the 3-dimensional de Sitter space to be totally geodesic or spherical.